On the Problems of the Humanization of Criminal Legislation - E. V. Gustova (Сибирское юридическое обозрение)
The article reveals the concept of humanization of legislation, analyzes the statistics of crimes to which decriminalization is applied. The last changes introduced into the Criminal Code of the Russian Federation are considered. Based on their analysis and analysis of drafted laws, the trends are determined not only by the humanization of criminal legislation, but also by significant liberalization. An assessment of these changes is given, features and possible difficulties in the application of new norms are analyzed, as well as those articles of the Criminal Code of the Russian Federation, to which significant changes have been made. Attention is paid to the imperfection of these changes, leading to destabilization of the legal provisions. The problems of rational application of criminal law norms of the Criminal Code of the Russian Federation are analyzed, negative factors that prevent their implementation are identified; formulated theoretical and practical provisions that contribute to the creation of a holistic concept of development and improving the effectiveness of legal techniques in criminal law; identified the main gaps and shortcomings in the design and application of criminal law.